Break point for the USTA : developing a strategic vision for the United States Tennis Association - Popp, Nels; Miller, Jason; Hambrick, Marion E. (London : Human Kinetics, Inc., 2013)
The United States Tennis Association is the National Governing Body for tennis in the U.S. and is comprised of three major divisions: (a) professional tennis, (b) player development, and (c) community tennis. The USTA's signature event and primary source of income is the U.S. Open tennis tournament. The organization currently faces several challenges, including two issues which have received significant media attention. The USTA currently lags behind several other nations in developing elite young players, despite the U.S. having large participant numbers. Also, financially-speaking, the U.S. Open is a highly successful event, but its largest show court lacks a roof, which has proven costly as several championship events have been postponed due to weather. The challenge of this case study is to develop a strategic plan for how the USTA can best use their resources to grow tennis in the United States.
Originally published in Popp, N., Miller, J., & Hambrick, M. (2013). Break point for the USTA: Developing a strategic vision for the United States Tennis Association. Case Studies in Sport Management, 2(1), 1-9. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; United States Tennis Association -- Case studies; Tennis -- Marketing -- Case studies